Pelatihan Penyusunan Laporan Keuangan Homestay Berbasis Excel di Desa Wisata Pinge Desa Baru Kecamatan Marga Kabupaten Tabanan - Ni Ketut Mareni; I Wayan Tuwi (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2023)
The Hospitality Accounting Management Study Program, one of the study programs at the Bali Tourism Polytechnic, carries out community service activities in Pinge Tourism Village, Baru Village, Tabanan 16 to 17 September 2022. The form of community service activity for the Hospitality Accounting Management Study Program in Pinge Tourism Village is The training with the theme